Leishmania lipophosphoglycan: how to establish structure-activity relationships for this highly complex and multifunctional glycoconjugate? - Forestier, Claire-Lise; Gao, Qi; Boons, Geert-Jan (Frontiers in Cellular and Infection Microbiology, 2015)
A key feature of many pathogenic microorganisms is the presence of a dense glycocalyx at their surface, composed of lipid-anchored glycoproteins and non-protein-bound polysaccharides. These surface glycolipids are important virulence factors for bacterial, fungal and protozoan pathogens. The highly complex glycoconjugate lipophosphoglycan (LPG) is one of the dominant surface macromolecules of the promastigote stage of all Leishmania parasitic species. LPG plays critical pleiotropic roles in parasite survival and infectivity in both the sandfly vector and the mammalian host. Here, we review the composition of the Leishmania glycocalyx, the chemical structure of LPG and what is currently known about its effects in the mammalian host, specifically. We will then discuss the current approaches employed to elucidate LPG functions. Finally, we will provide a viewpoint on future directions that this area of investigation could take to unravel in detail the biological activity of the specific molecular elements composing the structurally complex LPG.